RELIGIOUS ORGANIZATIONS AS A POLITICAL ACTOR IN BULGARIAN CIVIL SOCIETY - Nesterchuk, Olga; Trifonov, Nikolay; Grishin, Oleg (Revista Inclusiones, 2020)
The article discusses the political role of Bulgarian NGOs as participants in civil society in the political process and preserving the most important cultural components of the Bulgarian nation. Pays attention to the implementation of the interests of the population by religious communities at a local, national and supranational level. Discusses the social activity of the biggest religious organizations in Bulgaria – the Bulgarian Orthodox church and the Bulgarian Mufti, namely how they influence state bodies and support the population. The main conclusion is that religious organizations are the most important factor in Bulgarian civil society, because they have the largest number of members compared to other NGOs and accordingly, their activities to a large extend depend on preservation of traditions, identity, morality and the implementation of proper integration in the European structures of Bulgarian society. Their activity work allowed to build a specific model of religious-civil and state relations.